2014
DOI: 10.1109/tbme.2014.2322774
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cephalic and Extracephalic Montages for Transcranial Direct Current Stimulation—A Numerical Study

Abstract: While studies have shown that the application of transcranial direct current stimulation (tDCS) has been beneficial in the stimulation of cortical activity and treatment of neurological disorders in humans, open questions remain regarding the placement of electrodes for optimal targeting of currents for a given functional area. Given the difficulty of obtaining in vivo measurements of current density, modeling of conventional and alternative electrode montages via the finite element method has been utilized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…The variability across study design and parameters within MI and BCI performance, and across tDCS studies, in general, suggest significant avenues for future investigation to optimize stimulation for the target task. Recent computer modeling work has suggested that use of simulation pipelines may help improve optimal stimulation [5456]. Overall, the behavioral and electrophysiological results combined suggest that anodal tDCS is differentially affecting right and left hand motor imagination.…”
Section: Discussionmentioning
confidence: 99%
“…The variability across study design and parameters within MI and BCI performance, and across tDCS studies, in general, suggest significant avenues for future investigation to optimize stimulation for the target task. Recent computer modeling work has suggested that use of simulation pipelines may help improve optimal stimulation [5456]. Overall, the behavioral and electrophysiological results combined suggest that anodal tDCS is differentially affecting right and left hand motor imagination.…”
Section: Discussionmentioning
confidence: 99%
“…The electrode of interest was placed, depending on the group, over the left DLPFC (F3), the right DLPFC (F4), or the right IFJ (FC6h: midway between FC4 and FC6; see Figure 3). The reference electrode was always placed extracephalically (contralateral shoulder) to minimize its effect on the brain (Noetscher et al, 2014). Stimulation lasted 20 min with a constant current of 2 mA (current density = 0.057 mA/cm 2 ) and was faded in and out with an 8 s ramp.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that potential behavioural effects induced by the 'return' electrode are rarely measured does not alleviate the conceptual problem inherent in the idea of selectively influencing the function of a single brain region. This problem may be alleviated by the use of inert (e.g., extracephalic) return electrodes [38,39], asymmetrical electrode sizes [40], or more complex multi-electrode, high-definition (HD) tDCS montages [41].…”
Section: Motor -Evoked Potenɵalmentioning
confidence: 99%